Speech and Language Assessment Tools for Preschool and Primary School Children: Literature Review - Valeriya P. Lelik; Maria D. Dyachkova; Svetlana V. Dorofeeva ("Paediatrician" Publishers LLC, 2024)
The wide range of methods has been suggested for assessing the speech and language development in children. Therefore, the choice of suitable assessment tool is not always trivial. This article provides the overview of the methods used to examine Russian-speaking children, emphasises the parameters crucial for their comparison and, finally, choice itself. This review can be useful for researchers in the field of children's speech and language development, specialists using various tools for assessing children's speech in practice (pediatricians, speech pathologists, defectologists), as well as teachers and parents.